Role of Co-Operative Bank in Agriculture: A Case Study Of District Mohali, Punjab (International Journal of Scientific Research and Management (IJSRM), 2015)
The purposes of the study are to identify the beneficiaries of co-operative banks’ agricultural credit and to assess the impact for bank finances and the borrower-farmers.The impact has measured in terms of the benefits realized by the borrowers. These specific parameters that have been used for the purpose are: land utilization, extent of irrigation, cropping intensity, output pattern, cultural practices, input structure, gross and net farm incomes, employment pattern, saving pattern, and value assets like investment pattern,In addition to the identification and assessment of the benefits realized by the sample participants, an attempt is also made to examine farmers’ attitudes.